Intellectual capital and economic growth: evidence from some selected countries - Kalalto Gashe; Zerayehu Sime; Melkamu Mada (Cogent Economics & Finance, 2024)
The aim of this study is to explain the output growth across countries as an effect of intellectual capital growth. Defining intellectual capital as an integral of all the various intangibles, it argued to resolve the conceptual complexities and empirical inconsistencies. For this, the study defined the flow of new ideas as a function of change in intellectual capital level. Thus, it developed a model in which broad ideas predetermine the quality of capital and labor necessary for final goods production. The model was estimated using dynamic common correlated effect estimators for a panel of 29 countries from all income levels and geographic regions from 1990 to 2020. The results show a positive and significant contribution of national intellectual capital to economic growth. Hence, policymakers must enhance innovation in all spaces and phases of learning. The introduction of intellectual capital (IC) to explain economic growth, amidst unceasing complexities in conceptions and modeling intangibles, offers unprecedented significance for academics and policy issues. The concept of IC helps to encompass both technological and social innovation capabilities. Hence, for scholars interested in this field, the approach provides a novel model that explain the rate of flow of new technological and non-technological ideas of a given nation as a function of change in national IC level. This new idea generation function is also safe from 'scale effect', an inevitable problem facing all various generations of endogenous models. For economic policy makers the approach could simplify the conceptual complexities and also helps to look for domestic technological and non-technological capabilities before embarking on absorption of frontier technologies.
Keywords: O11; O32; O35; O36; O50; 330; ntellectual capital; innovation; economic growth; ideas